Formulation development and satisfaction assessment of herbal steam inhalation recipe: A pilot study - Moosigapong, Kotchakorn; Kaewmanee, Tarnita; Klayjaroen, Nattamon; Arusok, Wanwisa; Wandakhang, Wanmuhammadizham; Jaisamut, Patcharawalai (Health Science, Science and Technology Reviews, 2025)
Allergic rhinitis remains a chronic health problem. Despite the availability of effective treatments, there is a growing trend among patients to focus on easily accessible and safe herbal products. This pilot study aimed to develop and compare the formulation and physical characteristics of the herbal steam inhalation recipe in tablet and powder forms, and to evaluate the satisfaction among volunteers. Two herbal recipe formulations, each consisting of four sub-formulations with varying ratios of herbal powder and binder (Polyvinylpyrrolidone-K90: PVP-K90), were prepared. Stability was assessed through visual inspection, weight variation, and disintegration time. Among the tested formulations, herbal steam inhalation recipe 1 (formula 4: 75% (w/w) of herbal powder, 25% (w/w) of an 8% (w/w) PVP-K90 solution) and herbal steam inhalation recipe 2 (formula 2: 55% (w/w) of herbal powder, 45% (w/w) of an 8% (w/w) PVP-K90 solution) demonstrated optimal tablet formation, showing compact structures without cracks or moisture. Both formulations met pharmacopeial standards for disintegration time and tested positive for flavonoids and alkaloids. Satisfaction was evaluated in 30 volunteers using the Wilcoxon Signed Ranks Test at a significance level of p-value < 0.05. Results indicated that herbal steam inhalation recipe 1 (formula 4) in tablet form was rated significantly higher than its powder counterpart in terms of usability and convenience. Similarly, herbal steam inhalation recipe 2 (formula 2) in tablet form achieved significantly higher scores for usability, convenience, and overall satisfaction compared with the powder form. In conclusion, the study demonstrates that tableted herbal steam inhalation recipe formulations provide superior physical stability and greater user acceptance than powdered preparations, supporting the potential for developing the formulation into tablet dosage forms that are of high quality, convenient for healthcare facility and daily use.